Deconstruction of Communication Structures in the Digital Age: Public Hysteria and Government Panopticon - Rohimah, Afifatur; Bustomi, Abu Amar; Zuhriyah, Luluk Fikri; Jupriono, D. (The Journal of Society and Media, 2024)
The digital age and the pandemic have significantly impacted communication. The vast amount of data shared by internet users in virtual spaces has made issues related to the pandemic popular. Research was conducted in Indonesia to uncover the hidden meaning behind the pandemic's metanarrative. The study aimed to identify the government's interests behind the pandemic, dismantle them, and digitize communication. The research used Jacques Derrida's "Deconstruction" framework and qualitative approaches with descriptive-critical methods. It found that the pandemic has changed how people interact and communicate leading to significant social problems. These include mass hysteria and the emergence of a new social pathology called the information pandemic, characterized by fear, frustration, and stress. To control the phenomenon, the government has used a panopticon, which is a technique of power. The government strategy uses various forms of discourse, codes, rules, and symbols that trigger symbolic violence. However, the violence is in the form of soft and impressive discourse. The pandemic's impact on communication and society is far-reaching, and it is important to understand its effects.